PENGARUH KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP MOTIVASI DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN PADA PT. ASURANSI RAMAYANA (STUDI KASUS DI PT. ASURANSI RAMAYANA PEKANBARU, PADANG, MEDAN) - Mhd Suleman Hsb (Institut Bisnis dan Teknologi Pelita Indonesia, 2018)
This study aims to determine the effect of (1) leadership, (2) organizational climate to (3) motivation and its impact (4) the performance of employees. Survey method with quantitative approach. The population in this study is the Ramayana Branch All Staff Insurance Pekanbaru, Padang, Medan on PT Asuransi Ramayana as many as 70 people. To determine the sample size of the population census can be used a technique in which the entire population sampled. The instrument used to collect data variables leadership style, organizational climate, motivation and performance of employees by questionnaire Likert scale model. Validity test is done by using the formula Pearson Product Moment Correlation coefficients and reliability test using Cronbach Alpha. Data were analyzed using descriptive and inferential statistics for hypothesis testing digunakanstatistik trimming path analysis models. The results showed that: First, there is the influence of leadership on employee motivation as evidenced by the value of the path coefficient (ρx3x1) with a value of 0.406 and a correlation coefficient of 0.626 with a significance value of 0.007 or α <0.05. Secondly, there is the influence of organizational climate on work motivation in PT Asuransi Ramayana Branch Pekanbaru, Padang and Medan. This can be evidenced by the results of the calculation of the path coefficient (ρx3x1) with a value of 0.283 and a correlation coefficient of 0.598 with a significance value of 0.010 or α <0.05. Third: there is a leadership influence on the performance of employees of PT Asuransi Ramayana Branch Pekanbaru, Padang and Medan. This can be evidenced by the results of the calculation of the path coefficient (ρYx1) with a value of 0.234 and a correlation coefficient of 0.545 with a significance value of 0.019 or α <0.05. Fourth: There is the influence of organizational climate on employee performance (Y) in PT Asuransi Ramayana Branch Pekanbaru, Padang and Medan. This can be evidenced by the results of the calculation of the path coefficient (ρYx2) with a value of 0.109 and a correlation coefficient of 0.506 with a significance value or α 0.025 <0.05. Fifth: there is influence of motivation on employee performance of PT Asuransi Ramayana Branch Pekanbaru, Padang and Medan. This can be evidenced by the results of the calculation of the path coefficient (ρYx3) with a value of 0.362 and a correlation coefficient of 0.574 with a significan cevalue of 0.006or α <0.05. Results of this study are useful for improving employee performance through enhanced leadership styles, organizational climate and work motivation. Penelitian ini bertujuan untuk mengetahui pengaruh (1) kepemimpinan, (2) iklim organisasi terhadap (3) motivasi serta dampaknya terhadap (4) kinerja karyawan. Metode penelitian survei dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah Seluruh Staff Asuransi Ramayana Cabang Pekanbaru, Padang, Medan pada PT Asuransi Ramayana sebanyak 70 orang. Hasil penelitian menunjukkan bahwa : Pertama, terdapat pengaruh kepemimpinan terhadap motivasi kerja karyawan yang dibuktikan dengan nilai koefisien jalur (ρx3x1) dengan nilai 0,406 dan koefisien korelasi sebesar 0,626 dengan nilai signifikansi atau α sebesar 0,007 < 0,05. Kedua : terdapat pengaruh iklim organisasi terhadap motivasi kerja di PT Asuransi Ramayana Cabang Pekanbaru, Padang dan Medan. Hal ini dapat dibuktikan berdasarkan hasil perhitungan koefisien jalur (ρx3x1) dengan nilai 0,283 dan koefisien korelasi sebesar 0,598 dengan nilai signifikansi atau α sebesar 0,010 < 0,05. Ketiga : terdapat pengaruh kepemimpinan terhadap kinerja PT Asuransi Ramayana Cabang Pekanbaru, Padang dan Medan. Hal ini dapat dibuktikan berdasarkan hasil perhitungan koefisien jalur (ρYx1) dengan nilai 0,234 dan koefisien korelasi sebesar 0,545 dengan nilai signifikansi atau α sebesar 0,019 < 0,05. Keempat : Terdapat pengaruh iklim organisasi terhadap kinerja karyawan (Y) di PT Asuransi Ramayana Cabang Pekanbaru, Padang dan Medan. Hal ini dapat dibuktikan berdasarkan hasil perhitungan koefisien jalur (ρYx2) dengan nilai 0,109 dan koefisien korelasi sebesar 0,506 dengan nilai signifikansi atau α sebesar 0,025 < 0,05. Kelima : terdapat pengaruh motivasi terhadap kinerja karyawan PT Asuransi Ramayana Cabang Pekanbaru, Padang dan Medan. Hal ini dapat dibuktikan berdasarkan hasil erphitungan koefisien jalur (ρYx3) dengan nilai 0,362 dan koefisien korelasi sebesar 0,574 dengan nilai signifikansi atau α sebesar 0,006 < 0,05. Hasil penelitian ini berguna bagi peningkatan kinerja karyawan melalui peningkatan gaya kepemimpinan, iklim organisasi dan motivasi kerja.